MODAL SOSIAL UGASAN TOROP PADA PENGHAYAT KEPERCAYAAN UGAMO MALIM DI PUNGUAN BATUAJI BATAM - Finelita Saragi; Sri Wahyuni; Emmy Solina (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2022)
This study aims to determine the importance of social capital in society, especially for followers of Ugamo Malim and to maximize social capital in Ugasan Torop for its followers. This research method uses qualitative methods with a cultural approach. The results showed that the followers of the Ugamo Muslim faith in carrying out their torop duties as a form of gratitude that continues to this day have their own uniqueness. In every use and use of troop duties, it can be used by all households who adhere to the Ugamo malim belief without having to guarantee its use. Its use is also in terms of social assistance to help parmalim households who are in financial difficulty by paying attention to the norms that guide Ugamo malim's daily beliefs.